Toxic Leadership in Workplaces: Insights from Bibliometric, Thematic Analysis, and TCM Framework - Gupta, Amit; Chawla, Sonam (International Journal of Organizational Leadership, 2024)
Toxic leadership and its impact on the workplace represent significant issues in organizational research due to their adverse effects on both employee and organizational performance. Toxic leadership behaviors are important to understand since they harm the culture of the organization, undermine the well-being, health, morale, and productivity of employees, and impact organizational effectiveness. This article undertakes a comprehensive review of the literature on toxic leadership from the year 2000 to 2023, covering 480 articles on the subject, using a hybrid approach that combines bibliometric analysis along with keyword analysis, thematic analysis, and TCM framework. Through bibliometric analysis, we aim to identify key authors, articles, journals, organizations, and countries contributing to the research on toxic leadership. We categorize and analyze the various themes that encompass studies on toxic leadership. Additionally, by employing keyword analysis, we examine how the complexity and scope of research have evolved. Furthermore, we identify frequently utilized theories, contexts, and methodologies related to this phenomenon. Our primary contribution involves consolidating the extensive research conducted in the field of toxic leadership. Some of the potential areas of future research relate to gender differences, the impact of digital technologies, cross-cultural aspects, incorporating mixed-methods, longitudinal, and qualitative research to better understand the experience of toxic leadership, and examine the effectiveness of interventions to promote ethical leadership and mitigate toxic leadership.